2016
DOI: 10.14260/jemds/2016/1097
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practices About Nutritional Supplements of the Staff and Students of Universiti Kuala Lumpur - Royal College of Medicine Perak Malaysia

Abstract: BACKGROUNDThe rate of usage of nutritional supplement has increased tremendously over the past decades. In Malaysia, the dietary supplement market is about US $17.30/month. AIMThe aim of this study was to determine the association of knowledge, attitude and practice about nutritional supplements with socio-demographic factors of the respondents. METHODSThis was a cross-sectional study, conducted in 2015 at UniKL-RCMP, Malaysia. Convenient sampling was used. The data extracted from the questionnaires, entered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…The result was consistent with some studies in college from Tehran, Dammam, Pakistan, United Arab Emirates and South Europe (13,14,15,16). However, this result depicts a lower prevalence from previous studies where half of the respondents were DS users where the findings were reported from universities in India, Australia, China and also two universities from Malaysia (17,7,8,3,10).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…The result was consistent with some studies in college from Tehran, Dammam, Pakistan, United Arab Emirates and South Europe (13,14,15,16). However, this result depicts a lower prevalence from previous studies where half of the respondents were DS users where the findings were reported from universities in India, Australia, China and also two universities from Malaysia (17,7,8,3,10).…”
Section: Discussioncontrasting
confidence: 72%
“…Malaysia is one of the developing countries that reported was showing an increasing number of DS consumers, especially among adults as reported from the Malaysian Adult Nutrition Survey (MANS) 2014 (9). Consequently, the number also may increase among college students as evidenced by Al-Naggar and Chen (2011) and Haque et al (2016) (3,10). As the respondents are medical and health science students, they may prefer to consume a healthy diet from daily dietary intake instead of consuming DS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many pharmacists rely on their undergraduate education, which may not cover the intricacies involved in DS counselling adequately. 7 , 8 , 9 This issue is critical, as the contemporary healthcare landscape requires pharmacists to be well-versed in the interactions and contraindications of DSs, given the trend of consumer-led self-prescription. 8 …”
Section: Introductionmentioning
confidence: 99%